EFFORTS OF GUIDANCE AND COUNSELING SERVICES IN OVERCOMING DIFFICULTIES OF CAREER PLANNING STUDENTS CLASS XI IPA 5 SMAN DARUSSHOLAH SINGOJURUH ACADEMIC YEAR 2020/2021 - Heriberthus Wicaksono; Devani Rosalina S; Ratna Wulandari (International Jurnal of Education Schoolars, 2022)
Career planning is a learning process to prepare for future career choices by fostering careers and education in accordance with self-understanding and interests that must be taken in preparing to enter a career (job and position) and achieve career goals (dreams). Career Counseling is a process of assistance, service, approach to individuals so that they can identify and plan careers/advanced studies after graduating from school. The purpose of this study was to find out what factors caused the students of class XI IPA 5 of SMAN Darussholah Singojuruh to find it difficult to plan a career and to make efforts to help students who had problems planning a career. This research is a type of experimental quantitative research. Data was collected by using a one group pretest posttest. The pretest was given before the treatment, then the respondent was given treatment with Classical Guidance, then continued with the Post Test. The results of this study were analyzed through the IBM SPSS application and showed that the significance value before treatment was 35% while the significance value after treatment was 70%. This means that the treatment given by the author has the criteria of "Good" based on Likert Scale intervals. Therefore, 30% of these students need to be given special treatment in planning their careers after graduating from school having the criteria of "Good" based on Likert Scale intervals